Review on application of haptic in robotic rehabilitation technology - Mohammed Al-Dabas, Sari Abdo Ali; Miskon, Muhammad Fahmi; Shukor, Ahmad Zaki; Bahar, Mohd Bazli; Mohammed, Marwan Qaid Abdulrazzaq (Research India Publications, 2017)
Haptic is a science of touch tactile or kinesthetic. It is an interaction with humans and machines.The review is conducted by looking at, the different catagories of haptic teleoperation systems, the channel control architectures, the different challenges in implementing haptic technology, and the area of interest in the application of haptic and non-haptic robotic rehabilitation technology. The review reveal that, haptic teleoperation constitute of unilateral, bilateral and multilateral teleoperation systems, the control architectures are two channel, three channel and four channel control architectures, Haptic challenges can be categorized in five problems the stability, transparency, determining the force methods, scalingand frequency bandwidth. Finally, the review summarizes haptic and non-haptic rehabilitation systems. As a result, it’s been found that there are many rehabilitation systems but a few apply haptic. Haptic in rehabilitation is used in virtual haptic, but there are many opportunities can be benefit from haptic in real world rehab such as lower limb rehabilitation. In a conclusion, the gap in the area of haptic on robotic rehabilitation technology include, the limited attempt of applying haptic especially bilateral haptic control in robotic rehabilitation and particularly non for lower limb